2022
DOI: 10.31083/j.ceog4909209
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Physical Activity and Lumbopelvic Pain during Pregnancy: A Cross-Sectional Study

Abstract: Background: More than half of the pregnant women are affected by lumbopelvic pain (LPP) in their daily lives. Physical activity (PA) contributes to LPP relief. There are several reports on exercise habits, including the recommended activity intensity (moderate) and time spent (at least three times a week); however, only a few detailed reports on household/child-rearing and occupational activity are available. Therefore, this study explored the relationships between housework/child-rearing, occupational hours, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
1
2
0
1
Order By: Relevance
“…Pregnancy causes a forward shift in a woman's center of gravity, resulting in altered posture (Kawabe et al, 2022). Women who scored higher on the PPAQ likely spend more time on their feet throughout the day, and this altered posture may put additional pressure on their low back, resulting in pain (Kawabe et al, 2022). This reasoning is consistent with the positive trendlines seen in FIGURES 3 A, B, C, AND E, which demonstrated that subjective pain scores increased as PPAQ scores increased.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Pregnancy causes a forward shift in a woman's center of gravity, resulting in altered posture (Kawabe et al, 2022). Women who scored higher on the PPAQ likely spend more time on their feet throughout the day, and this altered posture may put additional pressure on their low back, resulting in pain (Kawabe et al, 2022). This reasoning is consistent with the positive trendlines seen in FIGURES 3 A, B, C, AND E, which demonstrated that subjective pain scores increased as PPAQ scores increased.…”
Section: Discussionsupporting
confidence: 67%
“…The unexpected result found in this study may be due to the physical changes that occur during pregnancy that differ from the general population. Pregnancy causes a forward shift in a woman's center of gravity, resulting in altered posture (Kawabe et al, 2022). Women who scored higher on the PPAQ likely spend more time on their feet throughout the day, and this altered posture may put additional pressure on their low back, resulting in pain (Kawabe et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hiperaktivitas yang dilakukan ibu hamil seperti berdiri dalam waktu yang lama dapat menyebabkan postur swayback dalam kurun waktu yang lama, dengan otot punggung yang tegang secara terusmenerus membuat ibu hamil menjadi rentang terhdap nyeri lumbal 4-5. Oleh karena itu, pengurangan aktivitas dalam melakukan pekerjaan dan pelatihan postur tubuh yang tepat pada ibu hamil sangat diperlukan agar dapat mengurangi beban pada tulang belakang lumbal (Kawabe et al, 2022).…”
Section: Pembahasanunclassified